Pelatihan Pembuatan Silase Kelompok Tani di Cireban Jaya Desa Kaduengang Kecamatan Cadasari Kabupaten Pandeglang - Kania Asri Liany; Pangesti, Raiza Tri; Wijaya, Gagah Hendra; Armelia, Vony; Syafiyullah, Radian; Magfira; Meindrawan, Bayu; Muztahidin, Nur Iman; Nurrofingah, Ulfa; Mardiyanti, Een; Nafisah, Ainun (BADAN PENERBIT STIEPARI PRESS, 2025)
The availability of forage as the primary feed for ruminant livestock often fluctuates due to seasonal changes, particularly in smallholder farming systems. This situation is notably evident in the Cireban Jaya Farmers Group located in Kaduengang Village, where farmers struggle to meet forage needs during the dry season. In response to this problem, a community service program was conducted to improve farmers' knowledge and skills in forage preservation by introducing silage-making techniques. The activity involved a series of methods, including socialization to raise awareness, group discussions to facilitate knowledge exchange, and practical demonstrations on how to process forage into silage. The silage was prepared using a mixture of fresh forage, rice bran, molasses, and EM4 as a fermentation starter. Through hands-on experience, farmers learned to identify characteristics of successful silage fermentation, which include a brownish color, a distinct sour aroma, and a compact texture. The silage produced was tested on local sheep, and results indicated positive acceptance after a short adaptation period. This confirms that silage can be an effective alternative feed solution during periods of forage scarcity and nutritional stress. The outcomes of the program revealed increased farmer competence in feed processing and a more resilient approach to livestock feeding. Moreover, the initiative helped reduce the dependence on seasonal forage availability, contributing to the sustainability of small-scale livestock farming. The training also encouraged collaboration among farmers, promoted local innovation, and supported the development of feed preservation strategies tailored to community needs. Overall, the training significantly enhanced local farmers’ capacity to manage feed resources efficiently, ensuring better productivity and animal welfare, particularly in areas prone to seasonal feed shortages and unpredictable climate conditions.